Preliminary Studies of Cassava Leavesâ Ability to Remove Dyes from Water - Chairunnisa Chairunnisa; Yuni Lisafitri (Journal of Mathematical and Fundamental Sciences, 2020)
Low-cost adsorbents from cassava leaves (CLP) were prepared by simply washing the leaf powder with deionized water. The adsorption of methylene blue (MB) from the aqueous solution was measured in order to examine the adsorbent performance. The effect of the pH of the solution was studied by varying pH from 2 to 10. The kinetics of MB adsorption onto CLP followed the pseudo-second-order kinetic model with a k-value of 0.087907 g mg-1 min-1 and 0.094081 g mg-1 min-1 for CLP before and after washing, respectively. The adsorption isotherm for both adsorbents followed the Langmuir isotherm model with qm values of 178.5 mg g-1 and 243.9 mg g-1. The existence of disturber ions was investigated by adding NaCl into the MB solutions at a variety of concentrations.